Identifying Moral Hazard in Car Insurance Contracts - Weisburd, Sarit (The Review of Economics and Statistics, 2015)
This paper capitalizes on a unique situation in Israel where car insurance coverage is often distributed as a benefit by employers. In our sample, employer-determined coverage resulted in an average $235 discount in accident costs. Using instrumental variable analysis on data provided by an insurance firm in Israel (2001–2008), we find that each $100 reduction in accident costs results in a 1.7 percentage point increase in the probability of an accident. At an average accident rate of 16.3 percent, this 10 percent increase in auto accidents can be interpreted as the effect of moral hazard on car accidents.